Colossians a short exegetical and pastoral commentary - Thiselton, Anthony C. 1937- (Eugene Wipf and Stock Publishers, 2020)
Intro -- Title Page -- Abbreviations -- Preface -- Part I -- Introduction -- Part II: Exegesis -- Introduction -- Doctrine -- Practice -- Personal Notes -- Bibliography.
Description based on publisher supplied metadata and other sources
Keywords: Bible-Colossians-Commentaries; Electronic books; Kommentar